Multimodality in English-medium nursing classroom interactions: A critical discourse analysis - Komilie Situmorang; Nurmala Elmin Simbolon; Santa Maya Pramusita; Pritz Hutabarat (Studies in English Language and Education, 2025)
English-medium instruction (EMI) continues to expand globally, yet multilingual classrooms remain linguistically complex, as students and lecturers navigate layered communicative challenges. While EMI research has advanced in general education settings, empirical studies grounded in healthcare-specific, discipline-oriented classrooms, particularly in non-English-dominant regions, remain limited. Addressing this gap, this study examines how multimodal resources including gestures, vocalizations, gaze, body movement, and first-language (L1) use are mobilized in EMI nursing classrooms at a university in Indonesia. Drawing on Critical Discourse Analysis (CDA) and ten hours of recorded classroom discourse, the study reveals how meaning is collaboratively constructed through multimodal ensembles that also shape power relations and pedagogical agency. A unique contribution of this research is the culturally embedded concept of Gado-Gado English, a metaphor for the dynamic blend of linguistic and semiotic resources used by teachers and students to cope with EMI challenges. Findings show that multimodal strategies foster inclusive participation, emotional engagement, and active knowledge construction in clinical learning contexts. By capturing naturalistic interaction in an underexplored EMI healthcare setting, this study offers both theoretical and practical insights into discipline-specific EMI pedagogy. Implications are drawn for EMI policy, curriculum design, and professional development, especially regarding the integration of multimodal resources as legitimate and empowering pedagogical tools.